FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN PROSES TURNAROUND PADA PERUSAHAAN MANUFAKTUR - Suhfriahtiningsih, Endah; Fidiana, Fidiana (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTEach company has experienced a decrease condition in the financial performance or it is commonly known as financial distress. To overcome this conditions, companies conduct some efforts to avoid bankruptcy or liquidation, which is commonly called as turnaround. There are several factors which determine the success of turnaround such as savings assets (asset retrenchment), free assets, debt restructure, and the replacement of the CEO (CEO turnover). This study is meant to analyze some factors which influence the ability of the company which experiences financial distress in achieving the success of turnaround. These factors are retrenchment assets, debt restructure, free asset and CEO turnover on manufacturing sector companies which are listed in Indonesia Stock Exchange in 2011-2014 periods. The Altman Z-score model is used to determine the recovery status of the company. The samplesare 38 companies which have been selected by using random sampling method. The results of data analysis are examined by using logistic regression analysis. Based on the result of the SPSS test states that asset retrenchment has negative coefficient value and significance values above 5%, so that asset retrenchment does not give any influence to the probability of company recovery conditions. Meanwhile, debt restructure statistically give influence to the probability of company recovery condition. Free assets and CEO turnover both have negative coefficient negative value so that free assets and CEO turnover does not give any influence to the probability of company recovery condition.Keywords: financial distress, turnaround, recovery, Altman z-score model